Peranan Guru dalam Membangun Karakter Siswa Kelas VI SD Negeri Rangat Nusa Tenggara Timur - Sari Andani; Nurhayati Selvi; Musbaing Musbaing (STKIP Andi Matappa Pangkep, 2022)
The aims of this study were to: 1) determine the teacher’s role in building the character of the sixth graders of Rangat State Elementary School, East Nusa Tenggara Timur, 2) find out the methods used by the teacher in building the character of the sixth graders of Rangat State Elementary School, East Nusa Tenggara Timur. This research uses qualitative research and phenomenological approach. Collecting data by using observation methods, interviews and documentation. Meanwhile, the data analysis used descriptive analysis by Miles and Hubermen consisting of: data reduction, data presentation and conclusion drawing. From the research, the following findings were obtained: 1) The role of teachers at SD Negeri Rangat in building character has been done by being a communicator, initiator, motivator and class manager. Class, with the existence of lesson plans when learning and mastering the material during the teaching and learning takes place make learning more active and efficient and with the emergence of new ideas carried out by teachers can increase students’ curiosity and creativity, 2) The method used by Rangat Elementary School teachers in building student character, Rangat Elementary School teachers have also shown exemplary teachers.